Higher prevalence of colonization with Gardnerella vaginalis and gram-negative anaerobes in patients with recurrent miscarriage and elevated peripheral natural killer cells. (April 2017) - Kuon, R.J.; Togawa, R.; Vomstein, K.; Weber, M.; Goeggl, T.; Strowitzki, T.; Markert, U.R.; Zimmermann, S.; Daniel, V.; Dalpke, A.H.; Toth, B.
Highlights: The vaginal microbiota differs between patients with elevated and normal NK cells. Colonization with Gardnerella vaginalis is associated with high peripheral NK cells. This might indicate a link between local inflammation and changes in immune parameters. Abstract: The role of vaginal infections in recurrent miscarriage (RM) is discussed controversially and screening is not recommended in international guidelines. Peripheral and uterine NK cells (pNK, uNK) play an important role in the establishment of a healthy pregnancy and are targets of immune diagnostics in RM patients. The aim of this study was to analyze the composition of the vaginal microbiota in RM patients and to correlate the findings to clinical characteristics as well as NK cell parameters. In total, n = 243 RM patients with ≥3 consecutive miscarriages were recruited between 11/2011 and 03/2016. Vaginal swabs were analyzed by microbiological culture. Further, a cervical swab was taken in n = 187 patients and the presence of Chlamydia trachomatis was evaluated by a molecular assay. Peripheral blood levels of CD45+CD3−CD56+CD16+ pNK (determined by four-color fluorescence flow cytometry) and CD56+ uNK (uterine biopsy, determined by immunohistochemistry) were analyzed. The prevalence of Gardnerella vaginalis colonization in RM patients was 19.0%, gram-negative anaerobes 20.5%, Candida species 7.9%, group B Streptococcus 11.0% and Enterobacteriaceae 14.8%. Commensal lactobacilli were absent in 14.5% of the women. Chlamydia trachomatis was detected in n = 1 case (0.53%). The prevalence of Gardnerella vaginalis and gram-negative anaerobes in RM patients with elevated pNK (>280/μl, n = 69) was significantly higher ( p = 0.012, p = 0.04) compared to patients with normal pNK ( n = 174). In conclusion, RM patients with elevated pNK suffer more often from colonization by Gardnerella vaginalis and gram-negative anaerobes . This might indicate an association between the vaginal microbiota, local inflammation, changes in immune parameters and miscarriage.